PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PT. JAYA BETON INDONESIA CABANG MEDAN - Aprilia Ariskha; M.Yamin Siregar; Isnaniah LKS (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to determine "The Effect of Financial Compensation and Non-Financial Compensation on Employee Performance of PT. Jaya Beton Indonesia Medan Branch. " This type of research is causal research (Causal Reaserch) which aims to test the hypothesis. The population in this study were 56 permanent employees. And by using saturated sample techniques, the number of samples used in this study were 56 respondents taken from all employees. Based on the results of the t test, it can be seen that the tcount on the financial compensation variable is 3,845, greater than the t table of 2,006 with a p-value that is sig 0,000 smaller than 0,05. Based on this value, the financial compensation variable has a positive and partially significant effect on the Performance variable. In the non-financial compensation variable, the tcount is 1,535 which is smaller than the table that is 2,006 with a p-value of 0,131 which is greater than 0.05. So the non-financial compensation variable does not have a positive and partially significant effect on employee performance. Based on the F test results, the Fcount value of 8,841 3.16 was obtained with sig 0.001 0.05 indicating Ho was rejected and Ha was received, meaning financial compensation and non-financial compensation had a positive and significant effect simultaneously on employee performance. The R2 value obtained is 0.242. To see the effect of independent variables on the dependent variable by looking at the R square table which shows 0.242. which as much as 24,2% of employee performance is influenced by financial and non-financial compensation and 75,8% is influenced by factors not explained in this study.